Pengembangan Media Pembelajaran Berbasis Quizlet untuk Meningkatkan Aktivitas Belajar Siswa pada Materi Alat Bersuci - Resty Aulia Nurmaya Ulfi; Jasiah Jasiah (STIKes Ibnu Sina Ajibarang, 2026)
The lack of interest of students in Fiqh learning is caused by the use of monotonous methods and media, which has an impact on the low activity of learning. To overcome this, interesting and interactive technology-based media innovations are needed. This research aims to develop a Quizlet-based learning media on the material of the Sacred Tools for class VII MTs Integrated Berkah Palangkan Raya to improve student learning activities. The research method uses the Researchand Development (R&D) approach with the ADDIE development model which includes the Analyze, Design, Develop, Implement, and Evaluate stages. The subjects of the study were 36 students of grade VII A. Data were obtained through observation and questionnaire of student responses to the use of Quizlet media. The results showed that learning using Quizlet obtained an average percentage of 89% in the